"It isn't you": Teachers' beliefs about inclusive education and their responses toward specific learning disabilities. Issue 4 (7th January 2022) - Woodcock, Stuart; Nicoll, Sandy
Abstract: Teachers' beliefs in inclusive education can be highly significant in the success of inclusive classrooms resulting in the performance outcomes of students. Teachers' understandings and expectations of students are important if students are to reach their potential. This study investigated 182 Australian secondary teachers' beliefs about inclusive education in relation to their causal attributions toward students with specific learning disabilities. This study was a quantitative study that used a survey instrument to measure teachers' attributional responses to students with and without specific learning disabilities. The findings show that teachers who believe in inclusive education report to be more positive/encouraging in their feedback towards students, feel greater sympathy toward them, as well as hold higher expectations toward the future than their counterparts. Teachers need to believe in inclusive education if students are to reach their potential at school. Highlights: Nearly half of the teachers in this study self‐reported positive beliefs toward inclusive education. Teachers within the first 10 years of their teaching careers reported more positive beliefs toward inclusive education. Teachers who believe in inclusive education report to be more encouraging in their feedback to students with specific learning disabilities. Greater sympathy was felt by teachers who believe in inclusive education toward students with specific learning disabilities. Teachers who believe in inclusive education hold higher expectations toward the future of students with specific learning disabilities.